Video gaming as digital media, play, and family routine: implications for understanding video gaming and learning in family contexts. Issue 4 (2nd October 2017) - Gee, Elisabeth; Siyahhan, Sinem; Cirell, Anna Montana
ABSTRACT: While a number of studies have investigated learning associated with video gaming in out-of-school settings, only recently have researchers begun to explore gaming and learning in the contexts of home and family life. This paper discusses three different frameworks within which we can situate video games and learning at home: (a) video gaming as digital media, (b) video gaming as play, and (c) video gaming as family routine. Each framework brings different issues related to learning into focus, and contributes new insights into the role gaming plays in the lives of children, adults, and families as a whole.